Advanced and versatile lignin-derived biodegradable composite film materials toward a sustainable world - Wang, Han-Min; Yuan, Tong-Qi; Song, Guo-Yong; Sun, Run-Cang (Green chemistry : an international journal and green chemistry resource : GC, 2021)
The excessive use of petroleum-based non-biodegradable plastic products has resulted in severe environmental pollution and ecological problems, which has stimulated the development of biodegradable and renewable alternative materials. Lignin, as the most abundant aromatic polymer with great biodegradability and biocompatibility, exhibits enormous potential for preparing various functional and sustainable materials as alternatives to plastics. Recently, lignin-derived biodegradable films have received extensive attention in both fundamental research and practical applications, and many significant achievements have been made in this field. Herein, the latest progress in the preparation and advanced applications of lignin-derived biodegradable film materials is summarized from a sustainability point of view. An introduction to the structural and chemical characteristics of lignin is presented first, and then the designs and advances of construction systems are reviewed based on the building matrixes, including lignocellulose, natural macromolecules, biodegradable synthetic copolymers, and other cutting-edge materials. In this review, the tailored applications of these film materials are mainly focused on sensors and responsive materials, energy storage systems, packaging, and biomedical materials. Finally, the main challenges of lignin-derived biodegradable film materials are presented, and potential development directions for sustainable and eco-friendly lignin-derived film materials are also proposed. This review summarizes the recent advances in fabrication strategies and versatile applications of lignin-derived biodegradable film materials from the viewpoint of sustainable development.